Pengembangan Bahan Ajar Flip Book Kontekstual Berbasis Android Pada Materi Akuntansi Persediaan - Gifar Fahrezi; Susanti Susanti (Universitas Hamzanwadi, 2021)
This development research aims to create teaching materials in the form of a contextual flip book on financial accounting subjects, especially Android based inventory accounting materials for Vocational High School class XI for competency in institutional accounting and financial expertise. The development of this flip book was tested by material experts, language experts, and graphic experts, and tested on 20 participants, namely students from class XI accounting and financial institutions at SMKN 1 Geger Kab. Madiun. The development research model used is 4D by Thiagarajan which consists of the define, design, develop stages without the dissemination stage. The analysis technique used in this research is descriptive qualitative and quantitative. The results of the validity analysis obtained the material feasibility of eighty five point two percent, language feasibility of ninety four point three percent and graphics of eighty seven point one percent with an average result of expert validation of eighty eight point eighty seven percent with the predicate very feasible. . The average result of student responses is ninety five point six percent with the very good category. So that the inventory accounting teaching materials developed with a contextual approach are very suitable for use in learning activities.